OBTENTION OF SOLID PHASES ADSORPTIFS BY SYNTHESIS AND TRANSFORMATION (Sciences & Technology. A, exactes sciences, 2013)
The industrial production of metals and metalloids had known a huge development in the last decades. Under the augmentation of world demand on refined products of consumption, things that has been traduced by some sub products, spatially refined iron in high furnaces. The byproducts named scoria, its source is El Hadjar plant, which constitutes an environmental and ecological problem. The work presented is a part of a huge project witch concerns the valorization of natural and artificial sub products, the agro-alimental, local herbs, for medical and cosmeticology uses. The research axe, specialized in preparing adsorbent solid phases is situated in our global project of research in which we are aiming to find a better use for the sub product of the High Furnace, (H.F)   in order to giveitother values. The memory of this publication spreads on a bibliographic study; followed by experimental works from witch we obtained good results.